2001
DOI: 10.21273/jashs.126.3.364
|View full text |Cite
|
Sign up to set email alerts
|

Can We Approach Complete Dependence on Foliar-applied Urea Nitrogen in an Early-maturing Peach?

Abstract: The suspected contributory role of soil fertilization to nitrate pollution of groundwater has encouraged exploration of novel fertilizer management strategies. Foliar-applied urea has long been used to supplement soil N applications, but there have been no apparent attempts to replace soil N applications completely in deciduous orchard culture. Two experiments were conducted to study the effect of foliar-applied low biuret urea on productivity and fruit growth of the early maturing peach [ Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
1
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 31 publications
1
24
1
3
Order By: Relevance
“…It has also been reported that complete dependence on foliar-applied urea N reduced fruit size of an earlymaturing peach (Johnson et al, 2001). However, we found no reduction in fruit size with foliar N application in this experiment.…”
Section: Discussioncontrasting
confidence: 49%
See 3 more Smart Citations
“…It has also been reported that complete dependence on foliar-applied urea N reduced fruit size of an earlymaturing peach (Johnson et al, 2001). However, we found no reduction in fruit size with foliar N application in this experiment.…”
Section: Discussioncontrasting
confidence: 49%
“…We used a low urea concentration (5 g/l) and multiple applications (7 sprays) during the growing season (from mid-May to mid-August, once every two weeks), while they sprayed with a high urea concentration (43 g/l) two-three times in October. A 50%:50% foliar:soil N combination treatment in their experiment maintained yield and fruit weight equal to the soil fertilized treatment, which suggested some soil-applied N was necessary for optimum fruit growth, but they did not indicate the threshold amount of soil-applied N required (Johnson et al, 2001). In our experiment, the ground was not covered when urea was sprayed, and about 12-15% of sprayed N fell to the ground as calculated from the volume of solution collected on the ground during the spray (data not shown).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Urea is the most widely used form of N for foliar applications because of its rapid absorption, low phytotoxicity, and high solubility (Bondada et al, 2001;Yamada et al, 1965). Johnson et al (2001) showed that N for normal growth of peach (Prunus persica Batsch.) buds, shoots, and roots can be supplied adequately by foliar urea applications during the growing season.…”
mentioning
confidence: 99%